Romanian Dendrocoelidae Hallez, 1892 (Platyhelminthes, Tricladida, Dendrocoelidae) Revisited: A Tribute to Radu Codreanu and Doina Balcesco - Anda Felicia Babalean (Biology, 2025)
This paper presents the current state of knowledge on the Romanian Dendrocoelidae as part of the European/Palearctic Dendrocoelidae, emphasizing the contributions of the Romanian zoologists Radu Codreanu and Doina Balcesco. The main objective of this work was to identify the knowledge gaps for future alignment with current standards. This article presents the species inventory and a short historical overview of the classical phylogenetic system and discusses some morphological characters used in the systematics of the group. This study also analyzes the arguments (and hypotheses) put forward by Codreanu, Balcesco, and other authors regarding the phylogenetic value of various factors, including (a) the position of the oviducts between the male atrium and the bursal canal (typical for Paradendrocoelum); (b) the eyes and the penial flagellum in relation to the palaeogeographical context governed by the Quaternary Glaciation; and (c) the point of view of Codreanu and Balcesco on the origin and composition of the actual Romanian Dendrocoelidae fauna. The major key finding is that the Dendrocoelidae species in Romania should be reinvestigated in an integrative way, and specific research needs and future directions are suggested.